SPACE-TEMPORAL ANALYSIS OF PHYSICO-CHEMICAL AND BIOLOGICAL VARIABLES OF WATER QUALITY IN THE ITAPECURU RIVER, NORTHEASTERN ATLANTIC HYDROGRAPHIC REGION, BRAZIL - Soares, Leonardo Silva; Lopes, Wilza Gomes Reis; Silva, Marcelo Henrique Lopes; Azevedo, James Werllen Jesus; Machado, Adilson Matheus Borges; Bandeira, Arkley Marques; Soares, Luciana Amorim; Castro, Antonio Carlos Leal de (Caderno Prudentino de Geografia, 2022)
The aim of the present study was to evaluate the surface water quality of the lower Itapecuru River in northeastern Brazil and investigate the spatiotemporal variations of physicochemical and biological variables. Twelve sampling campaigns at three-month intervals were conducted at five monitoring stations between 2012 and 2015. Significant changes were found from the upstream to downstream direction with regard to total suspended solids, transparency, turbidity and total iron, indicating that water quality was influenced by erosive processes in the sub-basins of the lower Itapecuru River. Iron (total and dissolved) and aluminum were frequently detected in the water, the concentrations of which were mainly related to the lithological characteristics of the region. No other metals or chemical pollutants, such as pesticides, hydrocarbons, phenols, free cyanide and artificial dyes, were detected in the section of the river investigated. The presence of thermotolerant coliforms and Escherichia coli indicate the direct discharge of sewage into the river. The principal component analysis demonstrated that 44.7% of the variability in the data was explained by the first three axes and the most representative variables were total suspended solids, iron (total and dissolved), transparency, total dissolved solids, temperature, true color and total phosphorus. The Itapecuru river is a strategic water resource for the development of the Northeast Atlantic Hydrographic Region of Brazil. The main pressure vectors identified in the research are associated with the discharge of sanitary sewage and the erosion processes of the sub-basins of the area of influence of the study, reducing the quality of the water in the stretch under investigation of the river. The information generated in the research is fundamental for the design of strategic actions for the planning and management of the Itapecuru river watershed.